ENHANCING ONLINE PRACTICAL COURSES IN MECHANICAL ENGINEERING: DEVELOPMENT AND ANALYSIS OF INNOVATIVE METHODS - Gabsi, Abd El Hedi; Mathlouthi, Safa; Ben Aissa, Chokri (Journal of Mechanical Engineering Education (Jurnal Pendidikan Teknik Mesin), 2023)
This research paper introduces three innovative approaches for delivering online practical courses in the field of mechanical engineering. With the increasing popularity of eLearning platforms, educators have been encouraged to adapt their teaching methods accordingly. However, teaching practical mechanical engineering courses online has posed significant challenges due to the reliance on machinery and hands-on equipment. This study represents a pioneering effort in proposing new methods to address these difficulties. The primary goals of this research are to establish the feasibility of conducting practical courses online and to provide solutions for enhancing the quality of such courses. To achieve these objectives, the study focuses on the development, application, and analysis of pedagogical approaches, virtual tools, and simulation software. The research was carried out with three student groups enrolled in two Tunisian Higher Institutes of Technological Studies. Based on the evaluations of these experiences, the implementation of new methodologies has led to a significant improvement in students' practical skills.